PENERAPAN METODE PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN PRAKARYA KELAS IX-1 SMP NEGERI 3 TEBING TINGGI - S., Rohimah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
TheÂ aim of this research is to increaselearning outcomeon application of craftthroughbased project learningmethod. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IX-1 Junior High School State 3 Tebing Tinggi which amounted to 37 students. This study used a qualitative descriptive analysis technique. The results showed that the use of project-based-learning method can improve student learning outcomeon application of craftprocessing aspect which characterized by increased mastery learning students, namely pre-cycle (72,97%), the first cycle (83,787%), cycle II (91,18 %) and complete learn the clasical equal to 91,18 %.Â Key Words : Project-Based-Learning, Craft ,Processing